Draft genome and multi-tissue transcriptome assemblies of the Neotropical leaf-frog Phyllomedusa bahiana - Andrade, Pedro (2022)
Amphibians are increasingly threatened worldwide, but the availability of genomic resources that could be crucial for implementing informed conservation practices lags well behind that for other vertebrate groups. Here, we describe draft de novo genome, mitogenome, and transcriptome assemblies for the Neotropical leaf-frog Phyllomedusa bahiana native to the Brazilian Atlantic Forest and Caatinga. We used a combination of PacBio long reads and Illumina sequencing to produce a 4.74-Gbp contig-level genome assembly, which has a contiguity comparable to other recent nonchromosome level assemblies. The assembled mitogenome comprises 16,239 bp and the gene content and arrangement are similar to other Neobratrachia. RNA-sequencing from 8 tissues resulted in a highly complete (86.3%) reference transcriptome. We further use whole-genome resequencing data from P. bahiana and from its sister species Phyllomedusa burmeisteri, to demonstrate how our assembly can be used as a backbone for population genomics studies within the P. burmeisteri species group. Our assemblies thus represent important additions to the catalog of genomic resources available from amphibians.